Preferensi, Pola Konsumsi Dan Tingkat Kepuasan Konsumen Minuman Kopi di Katama Coffee and Space Bandar Lampung - Fito Sailendra; Bustanul Arifin; Firdasari Firdasari (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This consumer behavior research aims to analyze consumer preferences toward product attributes (price, taste, flavor variants, packaging size), consumption patterns, satisfaction levels toward products and services, and the relationship between respondent characteristics and consumer satisfaction with coffee drinks at KATAMA Coffee and Space, Bandar Lampung.  Primary data were collected from 70 consumer respondents through validated questionnaires (r count > r table) and reliable (Cronbach Alpha > 0.6).  This study employed conjoint analysis for preferences, descriptive quantitative analysis for consumption patterns, Customer Satisfaction Index (CSI) for satisfaction levels, and Spearman Rank correlation test for characteristic relationships.  Research findings indicated the highest consumer preference for the combination of very aromatic scent, strong taste, Butterscotch Latte variant, and location with complete facilities (highest utility 4.007), with relative importance levels, flavor variant (32.711%), aromatic scent (31.198%), location (22.121%), taste (13.970%). Consumption patterns were dominated by purchasing 1 Butterscotch Latte item per visit (frequency 1x/week), conducted in the evening (>19:00 WIB), duration >2 hours, for relaxation purposes with friends/family. Consumer satisfaction reached CSI 78.83% (satisfied category), with the highest score on cleanliness (WS 61.79) and lowest on parking availability.  Spearman Rank test showed significant relationships (sig.<0.05) between education (r=0.285), occupation (r=0.268), income (r=0.247) with satisfaction levels, while gender and age were insignificant.  Respondent characteristics comprised mostly females (58.57%), aged 17-25 years (94.28%), students (84.29%), monthly income Rp500,000-1,500,000 (44.29%).